Enforcement of labor market regulations: Heterogeneous compliance and adjustment across gender - Mariana Viollaz (IZA Journal of Labor Policy, 2018)
This paper explores microdata from Argentine household surveys to analyze how changes in the enforcement of labor regulations affect the compliance level and other labor outcomes among men and women. Using information of the highly decentralized labor inspection system in Argentina, I construct an enforcement measure with variation at the province, sector, and time level (share of inspected firms) which I instrument using a measure of the arrival cost of labor inspectors to the firms. The main findings reveal that when enforcement increases, the compliance with mandated benefits and formal wages increase among men, while informal wages decline. Among women, the compliance level declines jointly with informal wages. These heterogenous impacts are explained by labor regulations that make formal and informal men more substitutable in the production process than formal and informal women.
Keywords: J16; J63; J88; K31; 330; Enforcement of labor regulations; Compliance with labor regulations; Gender; Argentina